Ruang Edukasi Politik Masyarakat: Wawasan dari Capres-Cawapres dalam Program Kampanye Pemilihan Presiden 2024 - Prakoso, Bayujati; Fatharani, Rachela Belinda; Illahi, Fajar Kurnia; Realita, Era; Himmah, Rif’atul (Fakultas Ilmu Sosial dan Ilmu Politik Unwahas, 2024)
Social media has become one of the primary media for political campaign activities, especially in the 2024 presidential election. This research tries to analyze how audience see the election dynamics and campaign programs of the candidates. Qualitative approach by utilizing Netlytic and ATLAS.ti version 9 was used to analyze the comments on YouTube. Researchers collecting some of comments from dialogue-based campaigns content on both platforms. The result shows that the audience respond positively to this kind of campaign content. Some of the keywords that appeared in the comments are leadership, intelligent, inspirational, public, education, etc. So, it can be said that audience positive response is a sign of success from the dialogue-based campaign that expected to make the public understand the programs of the candidates, as well as delivering the aspirations and problems they faced. On the other hand, in terms of the quantity of audience comments, 'Desak Anies' as a campaign activity/program is in the highest order, namely 29,902 comments, then in second place, 'Tabrak, Prof!' as many as 713 comments, then, in third place 'Slepet Imin' reached 416 comments, and finally 'Rembuk Ganjar' reached 68 comments. Apart from campaign programs, audience is free to comment on their sosial media about dynamics of the presidential election during the campaign period.Keywords: Audience Comments, Campaign Program, 2024 Presidential Election, Indonesia.